Roles of Universities in Realization of Industrial Economy in Moshi Urban, Tanzania: The Case of Moshi Co-operative University - Akaro, Bernadetha B; Mkulu, Dr. Demetria (International Journal of Humanities and Education Development (IJHED), 2020)
Universities are crucial agents of socio-economic development in any nation. They equip students with knowledge and skills which relate to industry, dissemination of knowledge and technical support to industry as well as fostering lifelong learning. Therefore, this study examined the roles of universities in realization of industrialized economy in Moshi Urban in Tanzania. It was guided by human capital theory. The study employed a descriptive research design. 84 students, 15 lecturers and 1 secretary of academic affairs were both randomly and purposively sampled to participate in the study. Questionnaire and interview were used to collect data. The questionnaire attained a Cronbach alpha coefficient of correlation of 0.70 which mean that it was reliable. Quantitative data were analyzed through descriptive statistics and qualitative data were thematically analyzed. The findings revealed that universities are linked to industrial economy and therefore charged with the role of conducting research, offering research courses and implementing projects to promote industrial development which is the cornerstone for successful industrial economy. The results of this study also indicated that in one hand the linkage between universities and industrial economy is not well realized due to a number of challenges, including inadequate resources, political interference, low support from university management and poor technology. On the other hand, the study found that adequate resources and curriculum reform to embrace practical education are among the available opportunities to empower universities towards realizing their roles in promoting industrial economy in Tanzania. The study recommends that the government of Tanzania should ensure conducive conditions and strategies to make universities excel in fulfilling their roles towards sustainable industrial economy.